Development of acrylonitrile-butadiene-styrene composites with enhanced UV stability - Santos, R. M. (2014)
Aiming to develop acrylonitrile–butadiene– styrene (ABS) composites with enhanced ultraviolet stability, a series of formulations were prepared by melt compounding and evaluated by different characterization techniques. The influence of rutile titanium dioxide (TiO2) and its combination with furnace carbon black (CB) on the viscoelastic properties of neat ABS was studied by dynamic mechanical analysis. An increase in the glass transition (Tg) dynamics ascribed to the rubbery phase as a function of exposure time was observed. A greater contribution of CB nanoparticles in combination with TiO2 to minimize the modifications on the Tg of the butadienic component was clearly seen. Quasi-static and spectrophotometry results are in good agreement, showing the efficiency of TiO2 submicron particles and CB/TiO2 against photo-oxidative degradation of neat ABS. A different behaviour was observed for modified ABS/TiO2 and ABS/ CB/TiO2 composites with light stabilizers, antioxidants and combinations of them. While the TiO2 efficiency was enhanced by the incorporation of combinations of light stabilizers and antioxidants, poor results were observed for modified ABS/CB/TiO2 composites as a consequence of antagonistic interactions. It was concluded that formulations of ABS/CB/TiO2 with light stabilizers and ultraviolet absorbers are unacceptable for common applications.